2008
DOI: 10.1182/blood-2007-09-108175
|View full text |Cite
|
Sign up to set email alerts
|

Leukemogenic mechanisms and targets of a NUP98/HHEX fusion in acute myeloid leukemia

Abstract: We have studied a patient with acute myeloid leukemia (AML) and t(10;11)(q23; p15) as the sole cytogenetic abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 49 publications
4
67
1
Order By: Relevance
“…Furthermore in one human AML the only characterised genetic change is a fusion of the prh gene with the nucleoporin gene Nup98 and this is thought to decrease the activity of endogenous PRH (11). We have shown that in a CML cell line, BCR-ABL activity indirectly results in the down-regulation of PRH transcriptional repression activity and the derepression of several PRH target genes including Vegfa, Vegfr-1, and Vegfr-2 (13).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore in one human AML the only characterised genetic change is a fusion of the prh gene with the nucleoporin gene Nup98 and this is thought to decrease the activity of endogenous PRH (11). We have shown that in a CML cell line, BCR-ABL activity indirectly results in the down-regulation of PRH transcriptional repression activity and the derepression of several PRH target genes including Vegfa, Vegfr-1, and Vegfr-2 (13).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, in human T-cell leukaemias associated with the aberrant expression of the LMO2 oncogene, elevated PRH expression is necessary for development of the disease (7,8). However, more generally, it is the disruption of PRH activity that is associated with a variety of diseases states (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the molecular mechanisms underlying the leukemogenicity of NUP98-PMX1, we quantitatively assessed Hoxa cluster gene expression in mouse stem cell virus-yellow fluorescent protein (MIY) empty vector control, PMX1, NUP98-PMX1 and NUP98-PMX1-N51Q-transduced lineage depleted, Sca1 þ (Lin-Sca þ ) BM cells. Similar to NUP98-HOXD13 (Palmqvist et al, 2007), NUP98-NSD1 (Wang et al, 2007) and NUP98-HHEX (Jankovic et al, 2008), NUP98-PMX1 strongly activated multiple Hoxa cluster genes, including Hoxa5 to Hoxa10, compared with MIY control and the non-leukemogenic PMX1 and NUP98-PMX1(N51Q) (Figure 7a, left panel). Furthermore, only NUP98-PMX1 activated expression of Bmi1, Flt3 and Cd34 (Figure 7a, right panel), genes associated with hematopoietic and LSCs (Wang et al, 2006;Argiropoulos and Humphries, 2007).…”
Section: Differential Transcriptional Properties Of Pmx1 and Nup98-pmx1mentioning
confidence: 94%
“…The nucleoporin gene NUP98 on chromosome 11p15 is involved in chromosomal rearrangements with at least 20 different partners (Slape and Aplan, 2004;Nakamura, 2005;Romana et al, 2006;Jankovic et al, 2008). NUP98 translocations have been described in de novo acute and chronic leukemias, as well as therapyrelated myelodysplastic syndrome and therapy-related acute myeloid leukemia (AML).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models developed to analyze the oncogenic activity of MLL and NUP98 fusions showed the overexpression of Hoxa9 and Meis1 in blast cells; 4,5,[15][16][17][18] in addition, Hoxa9 and Meis1 overexpression was associated with the emergence but not the maintenance of MLL leukemic stem cells. 9 We thus measured the expression levels of genes of the Hoxa cluster as well as the genes encoding for the HOX cofactors Meis1, Pbx1 and Pbx3 in BM cells from primary and secondary NUP98-HMGB3 recipients.…”
Section: Conflict Of Interestmentioning
confidence: 99%